4x-7=9x-5

Simple and best practice solution for 4x-7=9x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-7=9x-5 equation:


Simplifying
4x + -7 = 9x + -5

Reorder the terms:
-7 + 4x = 9x + -5

Reorder the terms:
-7 + 4x = -5 + 9x

Solving
-7 + 4x = -5 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-7 + 4x + -9x = -5 + 9x + -9x

Combine like terms: 4x + -9x = -5x
-7 + -5x = -5 + 9x + -9x

Combine like terms: 9x + -9x = 0
-7 + -5x = -5 + 0
-7 + -5x = -5

Add '7' to each side of the equation.
-7 + 7 + -5x = -5 + 7

Combine like terms: -7 + 7 = 0
0 + -5x = -5 + 7
-5x = -5 + 7

Combine like terms: -5 + 7 = 2
-5x = 2

Divide each side by '-5'.
x = -0.4

Simplifying
x = -0.4

See similar equations:

| 15x+60=165 | | 13.24-2.7p=5.5p-0.7 | | 5x+3.0=2x+3.3 | | 14+56=28w | | .66y+v=x | | 13x+84=175 | | 5n+72=3n-36 | | n-3=-n+3 | | 8a-2a= | | 9w=6.3 | | y=2/3(11)+4 | | -15=(5q-10)-5q | | 2(w-4)=26 | | (5y-7)^-4/3((5y-7)-3) | | 5x-22=3x+16 | | -1.5(x-2.25)=-10.55 | | -3p+4=-9(5p-10)-2(-5-5p) | | 1/8(a+3)=1/4(9-a) | | (n+3)5=3(2n-1) | | 6x6/7 | | 2/3G=-5/2 | | (6/x-4)/(2x-3)=0 | | 10y-6=4y+8 | | 8h=26 | | 7-(2z-5)=6-3z | | 2/3y+v=x | | v-9=214 | | 16+8x=25+15+3 | | -13x-13=2x-46 | | 220=4(-2+7x)+4 | | y=2/3(7)+4 | | -8(1+7m)=384 |

Equations solver categories